(untitled) (Research, Society and Development, 2022)
The difficulties of high school students to understand the abstract processes involved in the development of mathematical reasoning intrigues Mathematics teachers when they demand the use of a formal and rigorous language for the representation of the object under study. With the advent of digital technologies, the use of software makes it possible to represent the mathematical object through two-dimensional or three-dimensional graphics that facilitate student understanding. In this universe, the GeoGebra software stands out, as it allows the student to observe an infinity of properties that only using the classical language of mathematics would not be able to. The objective of this article is to verify to what extent the use of GeoGebra software can contribute to the understanding of the mathematical concepts of regression analysis in students of the 3rd of high school, of a public school in the city of Apuí-AM, southern region of the Brazilian state from Amazon. The methodology used was Didactic Engineering, which includes the confrontation of a priori analyses, with experimentation and a posteriori analyzes of a didactic sequence. The results revealed that the use of GeoGebra software can be effective for learning Statistics content, as it has been proven for Geometry and Trigonometry. Its use goes beyond performing calculations arranged in tables, as electronic spreadsheets already do. Its differential is the functionalities for carrying out the conversion from algebraic language to graphics and imagery languages, and vice versa.